PENGARUH KETERLIBATAN PEMAKAI, KAPABILITAS PERSONAL SERTA PROGRAM PENDIDIKAN DAN PELATIHAN PEMAKAI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERATING PADA BANK PERKREDITAN RAKYAT DI KABUPATEN KENDAL - Tofan Gilang Pratama, 13.05.52.0011; Srimindarti, Ceacilia (Students' Journal of Accounting and Banking, 2017)
The purpose of this study is to analyze the effects of participant of user, ability of user, traning and education of user on Accounting Information System (AIS) with complexity task as a moderating variable. The sample is taken by purposive sampling method, and fulfill the sample selection criteria. Relationships between variables or effects described by using multiple regression analysis and regression moderation analysis. The results of this study is that participant of user variables have a significant positive effect on Accounting Information System (AIS), ability of user have a significant positive effect on Accounting Information System (AIS), traning and education of user have a significant positive effect on Accounting Information System (AIS). Complexity task is able to moderate the influence of participant of user to Information System (AIS), Complexity task is able to moderate the influence of ability of user to Information System (AIS), and Complexity task is unable to moderate the influence of traning and education of user to Information System (AIS).Keywords: Participant Of User, Ability Of User, Traning And Education Of User, Complexity Task And Accounting Information System (AIS)